Analisis Implementasi Sistem Informasi Pemerintah Daerah (SIPD) Di Badan Perencanaan Pembangunan Daerah Kabupaten Seluma - Cahnia, Anisa; Lorita, Evi; Imanda, Antonio; Kader, Bando Amin C. (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The aims this study was to determine the implementation of Regional Government Information System (SIPD) development planning agency of Seluma district. Through analysis of data and information obtained at the research location. This study was a qualitative study presented descriptively. The informants of this study were 4 informants. Data collection techniques used observation, interviews and documentation. Based on the results of the study and discussion using the theory of Edward III 1984 (in Tresiana & Duaji, 2019:59) there are 4 (four) indicators used, namely: 1) Communication: Communication between the BAPPEDA of Seluma Regency and the Ministry of Home Affairs and OPD/SKPD of the Seluma Regency government was carried out via letters, WhatsApp groups, Zoom Meetings or direct coordination. The submission of OPD/SKPD information required in the preparation of development planning documents is also complete and clear. Information data is submitted by inputting information data through the One Data Indonesia portal. 2) Resources: The resources available at the BAPPEDA of Seluma Regency are also quite good and fulfilled, the operator's ability was quite capable of operating regional government information system although not optimally due to the lack of training programs and other training for regional government information system operators at the Bappeda of Seluma Regency, the budget funds from the APBD are also sufficient and the facilities used in the implementation of regional government information system are also adequate. 3) Disposition: The attitude of the implementers at the BAPPEDA of Seluma Regency was quite good. Implementors already have a firm attitude and desire to implement regional government information system in preparing regional development planning documents. 4) Bureaucratic Structure: The bureaucratic structure in implementing regional government information system policies is quite good because it was in accordance with standard operating procedures (SOP), BAPPEDA Seluma district has the authority to prepare development planning documents, namely RPJPD, RPJMD, and RKPD, the preparation of which is through SIPD.